PENGARUH UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN, DAN NON-DEBT TAX SHIELD TERHADAP STRUKTUR MODAL PADA PERUSAHAAN TELEKOMUNIKASI DI BURSA EFEK INDONESIA - Krisnanda, Putu Hary; Wiksuana, I Gusti Bagus (E-Jurnal Manajemen, 2015)
This study aims to determine the significance of the effect of partial variable size companies, sales growth, and non-debt tax shield (NDTS) the capital structure on Telecommunications companies in Indonesia Stock Exchange 2010-2013. To solve the problem in this study used multiple linear regression analysis technique. In partial test (t test) with significance level (?) = 5 percent, indicating that the firm size variable has a negative and significant effect on capital structure, sales growth has a positive effect and no significant effect on capital structure, while the variable NDTS positive effect and significant impact on the capital structure of the telecommunications companies in Indonesia Stock Exchange 2010-2013.
Keywords: ukuran perusahaan; pertumbuhan penjualan; non-debt tax shield; struktur modal